S85 Reduction of CD68 macrophages causes gender specific spontaneous pulmonary arterial hypertension in mice. (15th November 2016) - Zawia, A; Arnold, N; Braithwaite, A; Pickworth, J; Hopkinson, K; Iremonger, J; Miller, G; Lawrie, A
Abstract : Introduction: Macrophages are proposed to play an important regulatory role in the pathogenesis of pulmonary arterial hypertension (PAH) as excessive infiltration detected around vascular lesions in patients and animal models. The exact 'causal' role for macrophages, and whether their presence or absence is required for the vascular remodelling seen in PAH remains unclear. Objectives: Using a novel inducible macrophage depletion model ( MacLow mouse) we aimed to determine the role of macrophages in pulmonary arterial remodelling associated with PAH. Methods: Macrophage depletion was induced in MacLow mice by administration of doxycycline, where macrophage-specific induction of the cytotoxic diphtheria toxin A chain (DTA) is driven by the CD68 promoter. Mice were phenotyped for PAH by echocardiography, closed chest cardiac catheterization and immunohistochemistry (IHC) after 6 weeks. To investigate the origin of the effector cells, male chimeric mice were generated, and the disease stimulated by inducing macrophage ablation with doxycycline. Furthermore, to study gender-specificity of the disease phenotype, MacLow mixed gender chimeric mice were produced, and macrophage ablation induced as previous. Results: Interestingly male but not female MacLow mice developed a PAH phenotype compared to controls (RVSP of 66.1 mmHg vs 24.5 mmHg, p < 0.0001, n = 5–8), associated with increased right ventricular Hypertrophy (RVH 0.264 vs 0.226, p < 0.001, n = 8) and pulmonary vascular remodelling. IHC analysis of diseased lungs demonstrated increased iNOS- |CD206+ |F4/80+ macrophages suggesting a M2-like macrophage population drive the PAH phenotype in these mice. The bone marrow transplant studies shows that bone marrow (BM) derived cells contribute in the development of the disease phenotype as wild type BM cells attenuate disease progression. Moreover, female BM transplanted into male mice alleviate but does not protect them from developing PAH. Conclusion: Development of PAH in male MacLow mice suggests that macrophages play a causal role in pulmonary vascular remodelling. Results suggest that the phenotype is driven by lung resident M2- like macrophages with a contribution from bone marrow derived cells. A study to examine the probable protective effect of Oestrogen is now underway to further investigate the implication of gender difference in the incidence of PAH in this model.